2007
DOI: 10.1038/sj.gene.6364386
|View full text |Cite
|
Sign up to set email alerts
|

LymphTF-DB: a database of transcription factors involved in lymphocyte development

Abstract: B and T cells develop following a similar early stepwise progression to later stages where multiple developmental options are available. These developmental regimes necessitate differential gene expression regulated by a large number of transcription factors (TFs). The resultant burgeoning amount of information has opened a knowledge gap between TF activities during lymphocyte development and a researcher's experiments. We have created the LymphTF database (DB) to fill this gap. This DB holds interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Meanwhile, many genes involved in these branches (i.e., IL1RN encoding IL1, IL1R1, IL1R2 encoding IL1R, MAPK11, MAPK13 encoding p38MAPK, JUN encoding c-JUN, FOS encoding c-FOS, MYC encoding c-MYC, STAT3 encoding STAT3) were also upregulated, indicating that they may promote hepatocyte G0/G1 transition of the cell cycle. These results are supported by Morello et al who have shown that MYC is the immediate early proto-oncogene that could rapidly express after partial hepatectomy and promote cells transition from G0 to G1 phase [14], and the research of Masato et al, who showed that STAT3 and NFIL6 promote HC G0/G1 transition after phosphorylation by ERK and JAK [31]. In addition, target genes such as CTGF, MED1, and SOX15 (Table 4) have also shown positive regulation of G0/G1 transition by Gene Ontology, which is consistent with our results in Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Meanwhile, many genes involved in these branches (i.e., IL1RN encoding IL1, IL1R1, IL1R2 encoding IL1R, MAPK11, MAPK13 encoding p38MAPK, JUN encoding c-JUN, FOS encoding c-FOS, MYC encoding c-MYC, STAT3 encoding STAT3) were also upregulated, indicating that they may promote hepatocyte G0/G1 transition of the cell cycle. These results are supported by Morello et al who have shown that MYC is the immediate early proto-oncogene that could rapidly express after partial hepatectomy and promote cells transition from G0 to G1 phase [14], and the research of Masato et al, who showed that STAT3 and NFIL6 promote HC G0/G1 transition after phosphorylation by ERK and JAK [31]. In addition, target genes such as CTGF, MED1, and SOX15 (Table 4) have also shown positive regulation of G0/G1 transition by Gene Ontology, which is consistent with our results in Fig.…”
Section: Discussionsupporting
confidence: 77%
“…To determine the activity level of each signaling pathway and its branches, we used the Et to analyze the signaling activity as described in the Materials and Methods section. To confirm the interaction relationships between G0/G1 signaling pathways and HC G0/G1 transition, transcription factors of G0/G1 transition signaling pathways constructed above were input into TRED and Lymph TF-DB [30,31] to find their downstream target genes. Then the Et value of G0/G1 transition activity was calculated according to the section "Analysis of gene synergy (Et)" above.…”
Section: Analysis Of Gene Synergy (Et)mentioning
confidence: 99%
“…genmapp.org), KEGG (www.genome.jp/kegg/pathway.html), and QIAGEN (www.qiagen.com/ geneglobe/pathways.aspx) (Salomonis et al, 2007;Antonov et al, 2010). Moreover, NF-κB signaling pathway-related genes, such as Nfkb, Nfkb2,Rela,Relb,, were input into TRED (http://rulai.cshl.edu/cgi-bin/TRED/tred.cgi?process=searchTFGeneForm), lymph TFDB (http:// www.iupui.edu/~tfinterx/activity.php) and into NF-kB (http://www.bu.edu/nf-kb/gene-resources/ target-genes/) to find out their downstream target genes in rat (Childress et al, 2007;Jiang et al, 2007), mouse and human, among which cell proliferation-related genes were identified with the NCBI database. In the end, the genes were reconfirmed through literature searches of pertinent articles.…”
Section: Identification Of Nf-κb Signaling Pathway-and Cell Proliferamentioning
confidence: 99%
“…The list of genes found during the initial search, was subsequently compared to and complemented with genes in the biological pathway maps found in GENMAPP (www.genmapp.org), KEGG (www.genome.jp/ kegg/pathway.html), and QIAGEN (www.qiagen.com/geneglobe/path ways.aspx) (Salomonis et al, 2007;Antonov et al, 2010). Moreover, NF-kB signaling pathway-related genes, such as NFKB1, NFKB2, RelA, RelB, and c-Rel, were input into TRED (http://rulai.cshl.edu/cgi-bin/TRED/ tred.cgi?process=searchTFGeneForm), LymphTF-DB (http://www.iupui.edu/tfinterx/activity.php), and NF-kB (www.bu.edu) (Childress et al, 2007;Jiang et al, 2007). This was done to find their downstream target genes in rat, mouse, and human, among which cell proliferation-related genes were identified with the NCBI database, and reconfirmed with published articles.…”
Section: Identification Of Nf-κb Signaling Pathway-and Cell Proliferamentioning
confidence: 99%